Predictive factors and outcomes of posterior segment intraocular foreign bodies - Choovuthayakorn J. (2014)
Purpose To identify the predictive factors for anatomical and visual outcomes in posterior segment intraocular foreign body (IOFB) patients managed by pars plana vitrectomy (PPV). Methods A retrospective chart review was performed for 77 patients, who had PPV for IOFBs removal between January 2001 and July 2007. Univariate and multivariate analyses were conducted to evaluate the predictive factors. Results The mean age of the patients was 33.4 years. The nature of IOFBs was mainly metal, with injuries most commonly caused by an electric grass trimmer. The mean time interval between injury and IOFBs removal was 30.7 days. The mean preoperative visual acuity (VA) was 1.82 logarithm of the minimal angle of resolution (logMAR), and mean final was VA 1.10 logMAR. From multivariate analysis, good visual outcome was correlated with the corneoscleral entry site, and poor visual outcome was correlated with the presence of relative afferent pupillary defect. Conclusion sIn noncombat IOFBs, most cases were work-related. Delayed IOFBs removal was acceptable when primary wounds were repaired appropriately and extensive antibiotics administered. Even though advancement in vitreoretinal surgery can reduce the frequency of blindness, further promotion and education on eye protection during work are needed. © 2011 Macmillan Publishers Limited. All rights reserved.